Manufacture of Biodegradable Plastics from Cassava Starch (Manihot Escullenta) with Variable Glycerol Plasticizers and Chitosan Reinforcement - Zihan, Nurul; Nugrahani, Ratri Ariatmi; Hendrawati, Tri Yuni (Journal of Applied Sciences and Advanced Technology, 2024)
Biodegradable plastic is an alternative environmentally friendly packaging material because it is made from renewable materials and is scientifically easily degraded by microorganisms and by weather. Renewable material that is abundant in Indonesia is cassava which has high potential as a raw material for making biodegradable plastics. Purpose This study was conducted to determine the process of making biodegradable plastic from cassava starch, knowing the effect of adding glycerol and chitosan to the mechanical properties of biodegradable plastics, and know the characteristics of biodegradable plastics from the best conditions. The process of making biodegradable plastic from cassava starch begins with mixing cassava starch with water and processing until starch dough is formed. Next, glycerol is added to the starch dough and mixed until homogeneous. The final stage is chitosan added to the mixture and stirred until well mixed. The mixture is then heated and molded according to the desired shape. Biodegradable plastics produced from a mixture of cassava starch, glycerol, and chitosan have good mechanical properties and can decompose naturally in the environment for the study variables with concentrations of glycerol 2%,4%,6%,8%,10% and chitosan 1%,3%,5%,7%,9% in a mixture of 100 ml. Mechanical tests such as tensile strength, percent elongation and biodegradation of biodegradable plastics are carried out on product characteristics. The result of this study was to obtain the highest tensile strength in sample 1 of 3.41 Mpa and had an elongation of 68%. While the highest elongation in sample 3 was 130% and tensile strength was 0.26 MPa. The highest biodegradation result in sample 1 was 31.70% and the lowest in sample 5 was 6.55%.